Blue light inhibits transforming growth factor‐β1‐induced myofibroblast differentiation of human dermal fibroblasts. Issue 4 (April 2014) - Taflinski, Leonie; Demir, Erhan; Kauczok, Jens; Fuchs, Paul Christian; Born, Matthias; Suschek, Christoph V.; Opländer, Christian
Abstract Transforming growth factor‐β1 (TGF‐β1) is the major promoter of phenotypic shift between fibroblasts and myofibroblasts accompanied by the expression and incorporation of α‐smooth muscle actin (α‐SMA). This differentiation is crucial during normal wound healing and wound closure; however, myofibroblasts are considered as the main effecter cell type in fibrosis, for example in scleroderma and hypertrophic scarring. As blue light has exerted antiprolific and toxic effects in several cell types, we investigated whether blue light irradiations with a light‐emitting diode array (420 nm) were able to affect proliferation and differentiation of human dermal fibroblasts (HDF). We found that repeated irradiation with non‐toxic doses significantly inhibits TGF‐β1‐induced differentiation of HDF into myofibroblasts shown by α‐SMA immunocytochemistry and Western blotting. Additionally, used doses reduced proliferation and myofibroblast contractibility measured by resazurin and collagen gel contraction assays. It could be demonstrated that blue light mediates cell toxicity by oxidative stress due to the generation of singlet oxygen. We postulate that irradiations at non‐toxic doses induce low‐level oxidative stress and energy‐consuming cellular responses, which both may effect proliferation stop and interfere with myofibroblast differentiation. Thus, targeting differentiation, proliferation and activity of myofibroblasts by blue light may represent a useful strategy to prevent or reduce pathological fibrotic conditions.